Analysis of Lifestyle, Advertising Effectiveness, and Instant Coffee Consumption among Peri-Urban Farmers: Analysis of Lifestyle, Advertising Effectiveness, and Instant Coffee Consumption among Peri-Urban Farmers - Moh. Djemdjem Djamaludin; Dewi Mutia Silmie (Journal of Consumer Sciences, 2021)
Coffee consumption is increasing because many types of coffee are circulating, such as instant coffee among the public. The instant coffee studied in this study is the Iwan Fals edition of instant coffee. This study aimed to analyse the lifestyle and effectiveness of instant coffee advertising on instant coffee consumption among peri-urban farmers in Bogor Regency. This study used a cross-sectional study design located in Cibungbulang District, Bogor Regency. The location was chosen purposive because it is a peri-urban area that has more than 20% of agricultural land. A total of 100 respondents in this study were selected using a purposive sampling method with the criteria of a farmer and in the last 12 months consuming and viewing Iwan Fals edition coffee advertisements. The results of this study found that the maker's lifestyle is the most (32%) owned by the respondents. The effectiveness of instant coffee advertising in this study is included in the effective category (3.54). The results showed a relationship between gender, believing lifestyle, trying hard lifestyle with instant coffee consumption. The influence test results found an influence of male gender and lifestyle beliefs on instant coffee consumption. In general, respondents are classified as effective in consuming coffee because of their lifestyle and increase energy.